SCIENCES AND VALUES - Ioanes Rakhmat (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2014)
The separation of moral values and sciences is an illusion resulting from the incorrect view that only religions can produce morality. It is said wrongly that sciences concern only with facts and theories, not with values; only religions are able to deal with values. We know that ancient humans for a very long time were able to live morally even though they had no religions. We in the modern era are therefore able too even more. Using our modern sciences, mind, life experiences, and intuition, we too can construct secular moral views regarding everything to direct us in our complex lives.